Experience Gained in Mechanization of Frozen Ground Work - Sinyakov,V. I. (1974)
Superhard alloy teeth for excavating equipment used in working frozen ground and permafrost are illustrated. Types of equipment and techniques of use in various types of excavation work are illustrated and sample operating costs are given (in rubles). Numerous specific recommendations for improvement of the equipment are presented. Trans. of Stroitelnye i Dorozhnye Mashiny (USSR) n11 p13-14 1971.